Group classification of equations of axion electrodynamics - Brahinets, O.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
We carry out the group classification of axion electrodynamics models with axiom field self-action. To do this, we first classify the interaction functions that correspond to non-equivalent symmetry groups and find these symmetries. Some exact solutions that are interesting from a physical point of view.